2023
DOI: 10.20344/amp.18692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictive Factors of Exclusive Breastfeeding in the First Six Months of Life

Abstract: Introduction: Exclusive breastfeeding (EBF) is currently recommended until six months of age. The Baby-friendly Hospital (BFH) initiative an international program to promote breastfeeding, was launched in Portugal in 1994. The aim of this study was to identify the prevalence and factors influencing breastfeeding in the first six months of life and to compare the results with a study carried out in 1999 including population from the same geographic area.Material and Methods: A prospective, longitudinal and obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In step 9, it is recommended to support mothers in breastfeeding and inform them about the risks of using pacifiers and bottles. A study found an association between exclusive breastfeeding cessation, delayed skin-to-skin contact, and pacifier use [7]. At 6 months postpartum, the risk of nonexclusive breastfeeding was lower for infants who were exclusively breastfed for the first 48 h postpartum and were not given a pacifier or bottle [8].…”
Section: Introductionmentioning
confidence: 99%
“…In step 9, it is recommended to support mothers in breastfeeding and inform them about the risks of using pacifiers and bottles. A study found an association between exclusive breastfeeding cessation, delayed skin-to-skin contact, and pacifier use [7]. At 6 months postpartum, the risk of nonexclusive breastfeeding was lower for infants who were exclusively breastfed for the first 48 h postpartum and were not given a pacifier or bottle [8].…”
Section: Introductionmentioning
confidence: 99%
“…1 The discontinuation of exclusive breastfeeding is associated with delayed skin-to-skin contact, Neonatal Intensive Care Unit admission, pacifier and artificial teats use, mother's return to work earlier and lower education levels. 2 Racial and ethnic disparities in paid and unpaid workloads of mothers, and the relationship between components of job quality and duration of mother's own milk provision. 3 However, returning to work, insufficient breast milk, misconceptions about breastfeeding, and interference with social life were the barriers for mothers to breastfeed continuously.…”
mentioning
confidence: 99%